Neighbourhood deprivation and adult adiposity in South Africa - Dube, Masimba (Department of Public Health and Family Medicine, 2019)
Over the past three decades there has been a significant increase in adiposity - prevalence of accumulation of excess fat around some human organs - globally. This has been characterised by an increase of body mass index (BMI) among men and women. In Sub-Sahara Africa, South Africa has one of the highest prevalence of obesity and the country currently experiences some epidemiological transitions. Excess adiposity is a major risk factor for a number of non-communicable diseases creating a burden for individuals, families, the health care system and society at large (Colditz, 1999). Therefore, there are both direct and indirect costs that can be averted by effectively controlling the obesity epidemic. Still this can only be achieved when there is a good understanding of its determinants. This study sought to investigate association between neighbourhood deprivation and adult adiposity (a combination of body mass index and waist circumference), the association of neighbourhood deprivation and body mass index and waist circumference individually and to examine individual and household level determinants impacting adult adiposity. The study utilised the South African National Income Dynamic Survey (NIDS) 2012 (wave 3) and the ward level South African Index of Multiple Deprivation 2011 (SAIMD 2011) produced by Southern Africa Labour and Development Research Unit (SALDRU) and the Southern African Social Policy Research Institute/Insights (SASPRI) respectively. Individuals with high body mass index (BMI ≥ 25kg/m²) and an expanded waist circumference (WC ≥ 102cm for men and WC ≥ 88cm for women) were considered as having high adiposity. Multilevel logistic regression was used for data analysis due to hierarchical nature of the data to allow simultaneous examination of the impact of some socio-economic factors influencing adiposity. The results showed that individuals that were living in districts that are in quintile 3 (OR= 0.659; 95% CI 0.461, 0.942) of the multiple deprivation score had significantly lower odds of having high adiposity as compared to those living in the least deprived districts. Those living in districts that are in quintiles 3 (OR= 0.652; 95% 0.449, 0.945) and 4 (OR= 0.621; 95% 0.393, 0.983) of the multiple deprivation score were at significantly lower odds of having high BMI as compared to those living in the least deprived districts. When the analysis was stratified by gender the results showed that women living in districts in that are in quintiles 3 (OR= 0.654; 95% 0.450, 0.951) and 4 (OR= 0.624; 95% 0.394, 0.986) of the multiple deprivation score were at lower odds of having high adiposity as compared to women living in the least deprived district. The results for men on the other hand showed no association between adiposity and district level deprivation. Our results show that individual level characteristics and neighbourhood level deprivation regardless of how far distal has an impact on adiposity. Neighbourhood affluence seems to be a buffer that promotes weight gain. The impact of neighbourhood deprivation on adiposity is stronger among women as compared to men. However, further studies that employ a smaller area metric of analysis (preferably ward level) are required to better inform policy prescriptions of neighbourhood deprivation and adiposity.